2020
DOI: 10.1016/j.jjcc.2020.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Upper gastrointestinal bleeding in Japanese patients with ischemic heart disease receiving vonoprazan or a proton pump inhibitor with multiple antithrombotic agents: A nationwide database study

Abstract: Antiplatelet agents including low-dose aspirin (LDA) or adenosine diphosphate (ADP) receptor antagonists are widely used for the prevention of cardiovascular events. However, antiplatelet agents increase the risk of bleeding associated with mucosal breaks in the gastrointestinal (GI) tract [1,2]. Because GI bleeding is independently associated with mortality and ischemic compilations, and temporary cessation of antiplatelet agents increases the risk of mortality, GI bleeding prevention is important during ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Contrary to the recent meta-analysis, our result showed aspirin monotherapy after short DAPT has comparable bleeding events as compared to P2Y 12 inhibitor after DAPT. The reason why the comparable incidence of ischemic/bleeding events between aspirin and P2Y 12 inhibitor might be explained by high prescription of PPI, including potassium-competitive acid blockers [39] , and optimal medical therapy, i.e. statin (82.1% of population), for preventing atherothrombotic events in our cohort.…”
Section: Article In Pressmentioning
confidence: 79%
“…Contrary to the recent meta-analysis, our result showed aspirin monotherapy after short DAPT has comparable bleeding events as compared to P2Y 12 inhibitor after DAPT. The reason why the comparable incidence of ischemic/bleeding events between aspirin and P2Y 12 inhibitor might be explained by high prescription of PPI, including potassium-competitive acid blockers [39] , and optimal medical therapy, i.e. statin (82.1% of population), for preventing atherothrombotic events in our cohort.…”
Section: Article In Pressmentioning
confidence: 79%
“…In a study that compared vonoprazan and lansoprazole for the treatment of PUs, an acid-related disease, it was confirmed that both had similar tolerability profiles; vonoprazan was not less effective in treating gastric ulcer and duodenal ulcer [ 40 ]. Furthermore, in a previous study conducted in Japan, the non-inferiority of vonoprozan to PPI in the treatment of UGIB that occurred for 6 months in patients with ischemic heart disease receiving two or more antithrombotic agents was confirmed [ 41 ]. This may help reduce the risk of re-bleeding in patients with NVUGIB receiving OACs by maintaining an increased intragastric pH for a longer period.…”
Section: Discussionmentioning
confidence: 98%
“…As of mid-2023, there are no published manuscripts specifically addressing the use of P-CABs in NV-UGIB. A nationwide database study in Japan showed non-inferiority of vonoprazan compared to PPIs in rates of NV-UGIB in patients with ischemic heart disease receiving multiple anti-thrombotic medications [ 40 ]. There are multiple studies that comment on the effect of vonoprazan compared to PPIs for iatrogenic gastric or duodenal ulcers as a result of endoscopic submucosal dissection, with most finding an advantage with vonoprazan [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%